Dancing with myself, oh oh oh. Issue 2 (1st September 2013) - Ellis, Simon
This writing is an attempt to draw together a number of diverse ideas about information, curation, friendship and identity, and to consider these in relation to experiences of dancing on and around screens. Much of the writing might be thought of as playfully experimental, and in it I reflect on what it is like to be a choreographer in this rapidly changing time, and how technology might be valued, abandoned, questioned and even used as a tool for listening. As a choreographic artist working amongst the eclecticism and noise of contemporary dance influences and practices, I propose that acts and experiences of solitude and silence might help us make sense of the complex choreography of our social and artistic lives.